Analysis of the effect of the Ho Chi Minh City Tunnel settlement on the adjacent buildings - Nguyen Anh Tuan; Tran Duc Chinh; Nguyen Thanh Dat (КНУБА, 2017)
The paper aims to studying the effect of settlement of the Ho Chi Minh City Tunnel in soft soil condition on the nearby buildings due to tunneling by the Finite Element Method using Plaxis 3D Tunnel.
Keywords: Tunnel; soft soil; Finite Element Method; 539.3; 624.19(597.3)